2009
DOI: 10.1016/j.bone.2009.04.239
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 is essential for post natal osteogenesis but not for recruitment of osteogenic stem cells

Abstract: The effects of BMP2 on bone marrow stromal cell differentiation and bone formation after bone marrow ablation were determined using C57 BL/6J (B6) mice. Inhibition of BMP2 expression with lentiviral BMP2 shRNA prevented both mineralized nodule formation in vitro and bone formation in vivo, and blocked the expression of Runx2 and osterix, transcriptional determinants of terminal osteogenic differentiation. No effect was observed on the expression of Sox9, a transcription factor, which is the one of the first tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 53 publications
2
78
1
4
Order By: Relevance
“…Cells were co-transfected using Fugene 6 reagent (150 l) (Roche), and 3 plasmids: lentivirus plasmid, pcMV-VSV-G and pCMVdR8.2 dvpr at the ratio of 8:1:8. Non-Target lentivirus plasmid served as a negative control (24). The supernatant fluid was collected at 24-h intervals for three consecutive days and was replaced with fresh differentiation media (35 ml).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were co-transfected using Fugene 6 reagent (150 l) (Roche), and 3 plasmids: lentivirus plasmid, pcMV-VSV-G and pCMVdR8.2 dvpr at the ratio of 8:1:8. Non-Target lentivirus plasmid served as a negative control (24). The supernatant fluid was collected at 24-h intervals for three consecutive days and was replaced with fresh differentiation media (35 ml).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the other BMP members, BMP-2 is a dominant factor in postnatal skeletal homeostasis (15). It has been demonstrated that osteoprogenitor cells from BMP-2-deficient mice exhibit impaired differentiation into fully functional osteoblasts (16,17). Limb-specific BMP-2 knockout mice have spontaneous fractures that fail to resolve with time, and other osteogenic stimulatory molecules cannot compensate for the lack of BMP-2 (18).…”
Section: Introductionmentioning
confidence: 99%
“…Within BMPs, BMP-2 is an osteoinductive morphogen abundant in the bone extracellular matrix with proven activity on MSCs and defined roles in bone formation processes [24,25]. BMP-2 is extensively expressed in the growth plate, and its inhibition prevents osteogenic differentiation [26,27]. Likewise, the loss of BMP-2 in limb bud mesenchymal tissues leads to the inability to repair postnatal fractures [28], and the co-inactivation of both BMP-2 and BMP-4 results in severe osteogenesis impairment [29].…”
Section: Introductionmentioning
confidence: 99%